2012
DOI: 10.1007/s12298-012-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

Lack of genetic diversity of a critically endangered important medicinal plant Chlorophytum borivilianum in Central India revealed by AFLP markers

Abstract: Chlorophytum borivilianum is a traditional medicinal plant distributed throughout the tropics and subtropics. In the present investigation, AFLP analysis was used to assess the genetic similarity among 34 accessions. Nine primer sets of AFLP amplified 612 fragments, of which 246 fragments were found to be polymorphic. The average number of polymorphic bands per AFLP primer pair was 27.33. The amplified fragments ranged from 50 base pairs to 600 base pairs. Significant correlation was observed between total num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Among those, most of the studies were only of botanical importance (data retrieved on 08–11–2020). Moreover, the Botanical Survey of India has identified it as an endangered species in their “Red Data Book of Indian Plants.” It is predicted that the Indian forests may lose this valuable plant if conservation measures are not adopted ( Tripathi et al, 2012 ). Thus, due to high and diversified commercial importance, it has been instigated to reserve in the list of “threatened plants category.” Interestingly, biosynthesized nanoparticles (CRE-AgNPs) not only decrease the amount of dose required for the treatment but can also help to reduce the day-to-day growing demand of it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, most of the studies were only of botanical importance (data retrieved on 08–11–2020). Moreover, the Botanical Survey of India has identified it as an endangered species in their “Red Data Book of Indian Plants.” It is predicted that the Indian forests may lose this valuable plant if conservation measures are not adopted ( Tripathi et al, 2012 ). Thus, due to high and diversified commercial importance, it has been instigated to reserve in the list of “threatened plants category.” Interestingly, biosynthesized nanoparticles (CRE-AgNPs) not only decrease the amount of dose required for the treatment but can also help to reduce the day-to-day growing demand of it.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Botanical Survey of India has identified it as an endangered species in their "Red Data Book of Indian Plants." It is predicted that the Indian forests may lose this valuable plant if conservation measures are not adopted (Tripathi et al, 2012). Thus, due to high and diversified commercial importance, it has been instigated to reserve in the list of "threatened plants category."…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are various findings that confirmed the RAPD and AFLP markers have potential for identification and characterization of genetic relationship between the species of Chlorophytum and genotypes of C. borivilianum present in different geographical locations (Dwivedi and Sharma, 2011;Samantaray et al, 2011;Tripathi et al, 2012).…”
Section: Adulterantsmentioning
confidence: 97%
“…Genetic homogeneity is consistent with other studies that have shown no genetic variation in clonal plants in other plant families but not Acanthaceae, for instance Alternanthera philoxeroides (Amaranthaceae) (Xu et al, 2003) and Eichhornia crassipes (Pontederiaceae) (Li et al, 2006). Other studies have also revealed low levels of genetic diversity in clonal species or in populations of such species with more intense vegetative reproduction such as Microtis parviflora (Orchidaceae) (Peakall and Beattie, 1991), Haloragodendron lucasii (Haloragaceae) (Sydes and Peakall, 2002), Allium sativum (Amaryllidaceae) (Paredes et al, 2008), Iris sibirica (Iridaceae) (Kostrakiewicz and Wroblewska, 2008), Cypripedium calceolus (Orchidaceae) (Brzosko et al, 2011) and Chlorophytum borivilianum (Asparagaceae) (Tripathi et al, 2012).…”
Section: Genetic Homogeneity In C Nutansmentioning
confidence: 99%